Comparative Analysis of Sales Strategies and Market Challenges in the Solar Rooftop and Renewable Finance Sector: Insights from Leading Industry Players - Ronit Modi; Jigar Pandya; Jignesh Vidani (International Journal of Global Sustainable Research, 2025)
He solar rooftop industry and renewable energy finance sector are rapidly evolving, with various companies employing distinct sales strategies to drive market adoption. This study presents a comparative analysis of sales strategies and market challenges faced by sales executives from Solarium Green Energy Ltd, Tata Solar, Creditfair Finance, Waaree, and Jansmarth. The research explores key aspects such as target customers, sales approaches, challenges, required skills, and growth opportunities within these organizations. Findings reveal that while solar energy companies like Tata Solar, Waaree, and Solarium Green Energy focus on B2B and B2C solar adoption through direct sales, lead generation, and project bidding, financial institutions like Creditfair and Jansmarth specialize in solar loan approvals, credit risk assessment, and financial advisory services. Major challenges include market awareness, regulatory policies, pricing competition, loan processing delays, and customer creditworthiness. Essential skills identified include negotiation, financial analysis, CRM expertise, and strategic business development. This study provides insights into salary trends, career growth, and industry-specific requirements, helping stakeholders, policymakers, and job aspirants understand the sector’s dynamics. The findings underscore the need for enhanced policy support, financial accessibility, and sales innovation to accelerate solar rooftop adoption